New Periodic and Soliton Solutions of (2 + 1)-Dimensional Soliton Equation - Arbabi, Somayeh; Najafi, Mohammad; Najafi, Malihe (Journal of Advanced Computer Science & Technology, 2012)
By using the sine-cosine method proposed recently, we give the exact periodic and soliton solutions of the (2 + 1)-dimensional soliton equation in this paper. Many new families of exact traveling wave solutions of the (2 + 1)-dimensional soliton equation are successfully obtained. The computation for the method appears to be easier and faster by generalmathematical software.